Mayan Rights and Community Video: a collaborative Anthropology Experience - Flores Arenales, Carlos Y. (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2012)
An indigenous video archive in Santa Cruz del Quiché, Guatemala containing taped popular justice trials on the issue of Mayan rights inspired several anthropologists to develop a collaborative project along with indigenous mayors of the region. Santa Cruz del Quiché has been historically marked by crime, violence, and the absence of official law enforcement agencies. The following material analyzes the possibilities and difficulties of a collaboration of this sort, emphasizing and theorizing on the use of video in indigenous practices, legal pluralism, modernity, alternative epistemology, intertextuality and collaborative anthropology.